Study on the adsorption of Cr(VI) and atrazine by biochar - Jing, Ming; Ma, Zhaoyang (Frontiers in Earth Science, 2026)
The application of biochar in soil has demonstrated benefits in reducing greenhouse gas emissions, improving soil properties, enriching soil microbial communities, and effectively adsorbing pollutants to limit their mobility. This study focuses on the adsorption capacity of biochar for pollutants, specifically targeting Cr(VI) and atrazine. The research investigates the ability of biochar to immobilize Cr(VI) and atrazine within soil environments and explores how acidification of biochar can enhance its adsorption capacity for atrazine. The mechanism behind the enhanced adsorption capacity of acid-modified biochar is also examined. The results indicate that applying just 1% biochar can significantly improve the soil system’s capacity to immobilize Cr(VI). Fine-grained biochar shows a markedly higher adsorption and fixation capacity for Cr(VI), exhibiting up to three times the adsorption amount compared to larger biochar particles under certain conditions, with minimal desorption under acid rain leaching. Acidification was found to enhance the adsorption capacity of biochar for atrazine under certain conditions. Both the pre- and post-acidification biochar adsorption isotherms fit the Freundlich model, and adsorption capacity was notably affected by temperature, increasing with rising temperatures. The adsorption kinetics of pre-acid-modified biochar align with the Elovich model, whereas post-acidification biochar follows a pseudo-second-order kinetic model. The enhanced adsorption capacity of acid-modified biochar for atrazine is attributed to an increase in surface area, pore size, and pore volume, providing more adsorption sites and stronger van der Waals forces. Additionally, acidification alters the surface charge of biochar, leading to strong electrostatic attraction between biochar and atrazine.